HAK ASASI PEREMPUAN DALAM PERSPEKTIF HUKUM DAN AGAMA - Kurniawan, Nalom (Jurnal Konstitusi, 2011)
Increasing awarenes of the existing rights and factual social condition which is exactly manacling rights, especially women’s rights, has promoted cultural and moral struggle for activists who protect women’s rights. The wrong intepretations to the religion teaching and the strong pratilineal culture has degraded the women’s rights either in social life or positive norms of the laws